Substitution of Red Palm Oil Olein (RPOO) as a Source of Provitamin E in Grilled Meatball Sauce - Marini Yupita; Budiyanto Budiyanto; Hidayat Koto (Badan Penerbitan Fakultas Pertanian (BPFP), 2022)
Indonesia is the largest crude palm oil (CPO) producer in the world with a total production of 44,759 million tons in 2020 . One of the downstream products that can be made is RPOO which hasvitamin A and E content. This study aims to determine the effect of red palm oil olein (RPOO) substitution on the physical and organoleptic characteristics of grilled meatball sauce also to determine the vitamin E content in grilled meatball sauce. This study used a completely randomized design with RPOO substitution as a treatment (0%, 25%, 50%, 75%, 100%). The results showed that RPOO substitution had an effect on the physical characteristics of grilled meatball sauce, namely emulsion stability, organoleptic properties, and vitamin E content. The emulsin stability obtained was in the range of 89.33% -100% values. Grilled meatball sauce with 50% RPOO substitution is preferred as the best treatment by consumer best on overall. The vitamin E content in one servimg of the selectedt grilled meatball sauce is 20.5559 mc g, beyond recommended daily consumtion of vitamin E (15 mc g). Consuming 1 serving of grilled meatball sauce can meet the daily vitamin E needs for adolesence, adult male and female.